The Relationship Between Clinical Characteristics with Visual Outcome in Post Cataract Surgery at Tidore Islands City Regional Hospital - Izzatulhasanah, Izzatulhasanah; Wardana, Ganesa; Masrika, Nur Upik En (Universitas Negeri Gorontalo, 2025)
Introduction: Cataracts are a leading cause of blindness worldwide. The prevalence of blindness due to untreated cataracts remains quite high in Indonesia. In Eastern Indonesia, where there are limited healthcare facilities and scarce published data, this problem is particularly pronounced. Although cataract surgery is an effective intervention for restoring vision, postoperative visual outcomes can vary based on various patient-related clinical factors. No reported studies have addressed this issue in North Maluku. This study aims to analyze how clinical characteristics influence visual outcomes in patients after cataract surgery at Tidore Islands City Regional Hospital.Method: This research employed an observational analytical study with cross sectional design. This study used secondary data recorded at the Tidore Islands City Regional Hospital in 2020–2023 that meets the inclusion and exclusion criteria. The clinical characteristics assessed included age, gender, occupation, cataract stage, postoperative complications, and systemic comorbidities such as diabetes mellitus and hypertension. Visual acuity was measured using Snellen chart and converted into logMAR units for analysis and classification according to WHO criteria. Data analysis was performed using simple logistic regression.Results: Simple logistic regression showed no association between visual outcomes and age (p=0.089), gender (p=0.160), or occupation (p=1.395). Significant associations were observed for cataract stage (p=0.014), postoperative complications (p=0.004), and presence of comorbidities (p0.001).Conclusion: Age, gender, and occupation were not associated with visual outcomes. Cataract stage, postoperative complications, and comorbidities were significantly associated with outcomes. Diabetes mellitus was the most influential factor. Keywords: Cataract, cataract extraction, comorbidity, diabetes mellitus, visual acuity